MASA DEPAN HADIS DAN ILMU HADIS - Mosiba, Risna (Universitas Islam Negeri Alauddin Makassar, 2016)
In order to keep the hadith authenticity, Ulum al-Hadith should be positioned as a future of foothold patron. In fact, the rules embodied in Ulum al-Hadith must be built and reorganized in accordance with the needs of the times. In the study of hadith for example, the presence of the computer and its practical programs in doing Takhrij in hadith should be used as a tool. For the development and the future prospects of the hadith, then in addition to computerized systems it should also think about the need for other devices as a complimentary tool. By realizing these efforts, the hadiths as a source of law and way of life (hopefully) should still exist for the future of human beings. The innovation of hadith studies cannot be separated from the realignment of the hadith assessment methodology that should be adjusted with the times without amending the essence of the hadith itself although the methodology is inherited from Western scholars.